Implementasi Web Scraping Pada Situs Berita Menggunakan Metode Supervised learning - Hari Agus Prastyo, Edwin; Putra Eka Prismana, IGL; Wiratsongko, Radityo (Inovate, 2020)
Indonesia is one of the highest internet users in the world, including in the penetration of information on the internet, online news media. But in general news sites not only display news information, but Most sites also display other information such as advertisements and also forms of navigation that interfere with news site readers and interfere with reader comfort, from these problems this study aims to implement web scraping techniques with supervised learning methods and analyzing the form of DOM tree and XPath news sites. The supervised learning approach method is the method used in this study, which is one of the methods of machine learning. By combining these web scraping techniques with supervised learning, the aim is to be able to implement and optimize web scraping techniques to gather news information from various sites. To do basic web scraping that is knowing DOM patterns, XPath structure as a data model or selector at each site. The results of research in the form of a web scrap application that can retrieve news site content without copy paste and the data is stored in a database and displayed to the user application form for the reader without any ads and navigation that disturb the reader. Keywords: web scraping, supervised learning, XPath, DOM tree.